A conceptual study on hospital information system in public hospital of Bangladesh: Electronic medical record and clinical information system perspective - Haque, Mahbubul; Kayadibi, Saim; S. Rafsanjani, Khondakar; Billah, Mabruk (Canadian Center of Science and Education, 2013)
The empirical data is used in organizations all over the world which require the integration of some informational systems like Electronic Medical Record (EMR) and Clinical Information System (CIS); these concepts will discover with new form of Bangladeshi public hospital’s improvement in Information Technology (IT) sector. The objective of this conceptual paper is to review critically and identify the gaps in current literature aligning with Hospital Information System (HIS) and Electronic Medical Record (EMR), building relationship between EMR and CIS in terms of Bangladeshi public hospital; towards hospital’s effectiveness of service operator when public hospital plays an important role to keep the patients data. The proposed conceptual framework assists HIS providers to understand how EMR and CIS can contribute to improve the hospitals patient database. More over the paper presents an analysis in various aspects of EMR and CIS complying with a conceptual framework which can attract the researchers in Hospital information System field and public hospital management field for the better presences of information technology for the patients. Hospital Information System (HIS) is essential in hospitals especially which deals with high-quality healthcare treatments. HIS helps to improve patients care services. Thus, the Bangladesh Government has not introduced any kind of HIS for public hospitals of Bangladesh. Moreover, there is no study on HIS implementation in Bangladeshi public hospital.